(untitled) (Bangladesh Journal of Pathology, 2011)
Light emitting diode (LED) fluorescence microscopy offers well described benefits compared with brightfield microscopy by Ziehl-Neelsen stained sputum, even which are smear negative. We evaluated the diagnostic performance of fluorescence microscopy, using novel light-emitting diode (LED) technology as an alternative to the brightfield microscopy. The objective of this study was the role of LED fluorescence microscopy in diagnosis of smear negative pulmonary tUberculosis. This is a prospective study consisted of 50 smear negative patients, who were clinically suspected cases of pulmonary tuberculosis. All samples were stained by both ZN stain and Auramine stain and as a gold standard all were cultured on Lowenstein-Jensen Media. On evaluation of all sputum samples were found negative by ZN method but by auramine stain 16%, 20%, 20% cases were found positive by conventional fluorescence microscopy (CFM), LED and culture respectively. LED fluorescence microscopy is more useful test to distinguish the smear negative cases. It also provide an effective guideline to make decisions regarding judicious use of antitubercular drug therapy. Keywords: Smear negative Sputum; LED; CFM; Culture; Pulmonary Tuberculosis DOI: http://dx.doi.org/10.3329/bjpath.v26i1.9126 BJPATH 2011; 26(1): 3-6